The effect of two different strength training programs applied to male athletes in the various branches on some physical and physiological parameters - Fırat Akcan; Mursel Bıcer (Türk Spor ve Egzersiz Dergisi)
The purpose of this study is to research the physical and physiological effects of male athletes of the 8-week two different strength training programs. Three groups have been constituted from the volunteers among 18-30 ages who have participated in the study; Explosive Strength Group (ESG, n=12), Strength Endurance Group (SEG, n=12) and Control Group (CG, n=12). Explosive Strength and strength endurance training programs have been applied to ESG and SEG 8-week and 3 days in a week respectively.CG hasn’t been included in any training program. Height, body weight, back, leg and hand grip strength, flexibility, vertical jump, body fat percentage, 20m and 30m sprint and 20m shuttle run tests have been applied to the volunteers. Paired Samples T Test has been applied to the pre-test post-test measurements of the groups. One Way ANOVA Test and Tukey HSD test; besides Kruskal Wallis test and Dunnett’s T3 test have been used among the groups. Among the pretest post-tests of the groups ; heights, body fat percentage , relative and absolute back, leg and hand grip strengths, 20m and 30 m sprint, vertical jump, flexibility and at value of MaxVO2 at p lt;0.05 level significance has been determined. In Anaerobic strength values, in ESG and CG groups, significance at the level of p lt;0.05 has been determined. In the differences among the groups; heights, body fat percentage, absolute and relative back strength, relative right and left hand grip strengths, in 20m sprint and vertical jump values, significance has been determined at the level of p lt;0.05 when CG is compared among the groups, in the favour of ESG and SEG, when ESG and CG are compared about leg strength values, in the favour of ESG, when SEG and CG are compared about flexibility, in the favour of SEG. Significance hasn’t been determined between ESG and SEG groups. As a result, it can be said that there are positive effects of the Explosive Strength and strength endurance trainings on some physical and physiological parameters